Monitoreo del ruido ambiental para determinar los decibeles máximos en el terminal terrestre del cantón Latacunga, provincia de Cotopaxi, período 2013 - Alcarraz Rocha, Segundo Moisés (2015)
This study was based on the existing noise levels monitoring at the bus station in the Latacunga Canton. Its main objective was to determine the noise level in the environment and their decibels. In addition, the proposed mitigation plan to minimize noise levels. The noise, noise monitoring, regulation, measuring instruments and management plan aimed at reducing ambient noise as main components strategies. At Chapter I, it refers to the theoretical framework that strengthens research topics. At Chapter II, the methods and techniques to use them to serve as support for methodological, systematic, coherent and logical direction to take research to find the way, the tools and methodological guidance encourages states to develop the proposal. So, the qualitative and quantitative expressions for examination results are indicated....